The Role of ESG Disclosure, Firm Size, and Financial Performance on Firm Value in the Energy Sector on the Indonesia Stock Exchange - Dedi Sugala; Fattah, Vitayanti; Kasim, Muhammad Yunus; Utami, Ayu Putri (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of ESG disclosure, firm size, and financial performance on firm value in energy sector companies listed on the Indonesia Stock Exchange during 2021–2024. Using a quantitative approach, panel data regression was conducted in EViews on 19 companies selected through purposive sampling. The findings show that ESG disclosure has a negative and insignificant effect on firm value, while firm size has a positive but insignificant effect. Meanwhile, financial performance has a positive and significant effect on firm value, indicating that profitability remains the main factor considered by investors in valuing energy sector companies. Keywords: ESG Disclosure: Firm Size: Financial Performance; Firm Value